Analisis Dampak Politik Isolasi (Sakoku) Bagi Kehidupan Masyarakat di Jepang - Waruwu, Yosua Heman; -, Rani Arfianty (Undiksha Press, 2024)
Japan is a country that has a lot of history in it through a lot of growth and development as well as politics that existed in every era. Japan has one form of politics in it, namely: Sakoku politics. In the Sakoku political system there are no foreign communities, especially communities. Japan opposed the order of Shogun Tokugawa Ieasu to enter Japanese territory for foreigners and local people were not allowed to travel or leave Japanese territory. Research using qualitative methods, this research aims to understand and analyze through YouTube sources with the outline of the discussion being